The South American MicroBiome Archive (saMBA): enriching the microbiome field by studying neglected populations - Benjamin Valderrama; Paulina Calderón-Romero; Thomaz F. S. Bastiaanssen; Aonghus Lavelle; Gerard Clarke; John F. Cryan (Nature Communications)
Abstract The human gut microbiome is associated with numerous health outcomes, often in a region-specific manner. Unfortunately, global microbiome research remains profoundly imbalanced: over 70% of sequenced human microbiomes originate from Europe and North America, which together represent only 15% of the world’s population. To address this disparity, we developed saMBA—the largest archive of gut microbiomes from South America, one of the world’s most microbiome-diverse regions but also among the least studied. The archive comprises 33 studies, ~73% of which had not been included in any previous compendium. A total of 3382 samples were reanalysed, of which 2913 were successfully included after applying quality filters. By leveraging this resource, we reveal both high within-population diversity and between-population uniqueness in the continent, expanding our current understanding of the gut microbiome to be more globally representative. Additionally, saMBA reveals that much of the region’s gut microbiome diversity remains undercharacterised, and provides guidance for future sampling efforts to more accurately capture regional biodiversity. The framework used to build saMBA is compatible with existing global resources and is openly available, thus promoting the inclusion of other underrepresented populations to accelerate microbiome research globally.